Isolated vertebrae of brittlestars of the Family Klasmuridae Spencer, 1925 (Echinodermata: Ophiuroidea) in the Devonian of Bohemia (Czech Republic) - Hotchkiss,F.H.C.; Prokop,R.J.; Petr,V. (Journal of the Czech Geological Society, 1999)
Interesting rare isolated ophiuroid vertebrae have been discovered in washings from the so-called 'white beds' of Lower Devonian (Trebotov Limestone, Dalejan) of the Barrandian area. We interpret these vertebrae as belonging to a member of the Family Klasmuridae Spencer, 1925 (Order Stenurida Spencer, 1951; Suborder Scalarina Hotchkiss 1976). This is the first report of isolated vertebrae of these ophiuroids in the world. A short note on the Barrandian 'white beds' is also presented here
Keywords: Micropalaeontology; Echinodermata; Ophiuroidea; Klasmuridae; isolated vertebrae; phylogeny; Lower Devonian; Bohemia